(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article talks about pedagogical neology and related models, one of the main indicators of student social activity. This article covers in detail the issues of improving the social activity of students on the basis of pedagogical neonology in the system of higher education.